The anthelmintic efficacy of papaya latex in a rodent-nematode model is not dependent on fasting before treatment - Luoga, W; Mansur, F; Buttle, DJ; Duce, IR; Garnett, MC; Behnke, JM (Cambridge Univ Press, 2024)
Indexed by SCOPUS/WOS